Compliance to hygiene standard among vessel owners and crew on board of Pahang deep sea fishing vessels in Malaysia - Kemat, Norazizah (2018)
Fishing vessel is categorized as primary producer where vessel operators must ensure that measures to control environmental contamination are enforced and implemented. This study aimed to determine hygiene knowledge, attitude and practices among fishing vessel crews; to evaluate barriers and needs for on board hygiene implementation among vessel owners; to assess the microbiological quality of fish hold, fish tank and fish deck before and after loading operations; and to establish the relationship among socio demographic, hygiene practice as well as microbial quality of gloves surfaces. Data for knowledge, attitude and practices were collected from 70 fishing vessel crews using a structured questionnaire; Barriers and needs to implement current on board hygiene were assessed using a structured checklist among 17 vessel owners. Analysis of food contact surfaces on board (fish hold, fish tank, fish deck and gloves) were tested for total aerobic count, Escherichia coli, coliform, yeast, moulds and Staphylococcus aureus. Data were analysed using standard statistical method. The results showed that the vessel crews have good attitude (85.2%), sufficient knowledge (71.48 %) of on board hygiene, however they lack in practices (30.64%). There was a significant correlation between practices and knowledge (P = 0.000), indicating that hygiene knowledge influenced vessel crews hygiene practices but not their attitudes. Three major barriers were identified; comfortable with existing practices, less exposure on information from authority and difficulty to get public soft loan. These barriers were significantly correlated (P < 0.05) to education, experience, ethnic and training among the vessel owners. The hygiene level of all contact surfaces before cleaning activity was unacceptable based on the total aerobic count (> 5.0 CFU/cm2). The microbial load on all contact surfaces were found to be at moderate hygienic level for coliform (0.2 - 1.0 CFU/cm2) and yeast (1.0 - 5.0 CFU/cm2). For moulds, only fish tank and fish deck surfaces contained < 0.6 CFU/ cm2 (good hygienic level), while fish hold and gloves were of moderate level (0.6 - 1.6 CFU/cm2). The study also showed that after cleaning activity, hygiene level of all contact surfaces was still unacceptable for total aerobic count. All surfaces demonstrated a good hygienic level based on coliform, yeast and moulds counts, except for fish deck which was moderate for coliform. S. aureus was detected (< 1.0 CFU/cm2) on all surfaces during the study. Only coliform load was significantly correlated with training. A significant relationship between microbial load (total aerobic count, coliform and yeast) and poor hygiene practices was established (P< 0.05). This study provides an insight that training and awareness on good hygiene practices should be emphasized among vessel crews and owners.